Characterization of myocardial tissue in patients undergoing maintenance hemodialysis by quantitative echocardiography. - Morales, M A; Ferdeghini, E M; Pizzarelli, F; Piacenti, M; Dattolo, P; Pelosi, G; Distante, A; Maggiore, Q (Journal of the American Society of Echocardiography)
The uremic state affects myocardial structure, bringing about, among other things, interstitial calcium deposition. Abnormalities of myocardial structure can be assessed quantitatively and noninvasively during life by the analysis of the gray-level distribution of conventional two-dimensional echocardiograms. The aim of this study was to evaluate the role of quantitative echocardiography in providing information on myocardial structure in patients under maintenance hemodialysis and to relate the ultrasonic findings with abnormalities in calcium-phosphate metabolism. Forty patients undergoing dialysis without abnormalities in left ventricular regional and global function and 17 hypertensive patients with comparable left ventricular hypertrophy were studied. The distribution of the gray levels within a region of interest in the interventricular septum was analyzed off-line by an array processor-based computer. Compared with hypertensive patients, patients undergoing dialysis showed a greater myocardial echogenicity (mean 92 +/- 20 versus 72 +/- 15; p = 0.004) and a reduced homogeneity of distribution of gray levels (entropy 4.5 +/- 0.2 versus 4.2 +/- 0.2, p < 0.01; uniformity 0.010 +/- 0.003 versus 0.020 +/- 0.004, p < 0.005). In the same patients, a significant negative linear relation was found between entropy and calcium-phosphate product (r = -0.66; p = 0.001). Quantitative analysis of conventional two-dimensional echocardiograms allows the detection of a pathologic myocardial structure in patients under maintenance hemodialysis with normal left ventricular function. These abnormalities are related to disorders of calcium-phosphate metabolism and bear no relationship to the degree of left ventricular hypertrophy.